Quaternary megafauna from the Dnieper alluvium near Kaniv (central Ukraine): Implications for biostratigraphy - Ridush, Bogdan; Stefaniak, Krzysztof; Ratajczak-Skrzatek, Urszula; Kovalchuk, Oleksandr; Kotowski, Adam; Marciszak, Adrian; Polishko, Oleksandr (Elsevier Ltd and INQUA, 2021)
Subfossil remains of the Quaternary megafauna from two Ukrainian natural history collections stored at Kaniv Nature Reserve and the National Museum of Natural History NAS of Ukraine were examined. Most of the bones were collected in 1965–1966, in the building pit and the gateway of the Kaniv hydroelectric power plant. The fauna is represented at least by ten taxa (Gulo gulo, Mammuthus trogonterii chosaricus, Mammuthus intermedius, Coelodonta antiquitatis, Megaloceros giganteus, Alces alces, Bison priscus, Cervus elaphus, Capra cf. ibex, and Equus ferus). Skeletal parts are represented mainly by skulls, long bones, horns, and tusks. Based on the species composition of proboscideans, at least part of the faunal assemblage is dated by the end of the Middle Pleistocene (Dnieper Stage =Saale, Warta, MIS 6), but the majority of bones could be older or younger (Late Pleistocene and Holocene age) due to the alluvial origin of accumulation.
Keywords: Megafauna; Quaternary; Middle Dnieper area; Alluvium; Biostratigraphy